Podocytes maintain high basal levels of autophagy independent of mtor signaling - Bork, Tillmann; Liang, Wei; Yamahara, Kosuke; Lee, Philipp; Tian, Zhejia; Liu, Shuya; Schell, Christoph; Thedieck, Kathrin; Hartleben, Bjoern; Patel, Ketan; Tharaux, Pierre-Louis; Lenoir, Olivia; et al. (Autophagy, 2020)
While constant basal levels of macroautophagy/autophagy are a prerequisite to preserve long-lived podocytes at the filtration barrier, MTOR regulates at the same time podocyte size and compensatory hypertrophy. Since MTOR is known to generally suppress autophagy, the apparently independent regulation of these two key pathways of glomerular maintenance remained puzzling. We now report that long-term genetic manipulation of MTOR activity does in fact not influence high basal levels of autophagy in podocytes either in vitro or in vivo. Instead we present data showing that autophagy in podocytes is mainly controlled by AMP-activated protein kinase (AMPK) and ULK1 (unc-51 like kinase 1). Pharmacological inhibition of MTOR further shows that the uncoupling of MTOR activity and autophagy is time dependent. Together, our data reveal a novel and unexpected cell-specific mechanism, which permits concurrent MTOR activity as well as high basal autophagy rates in podocytes. Thus, these data indicate manipulation of the AMPK-ULK1 axis rather than inhibition of MTOR as a promising therapeutic intervention to enhance autophagy and preserve podocyte homeostasis in glomerular diseases. Abbreviations: AICAR: 5-aminoimidazole-4-carboxamide ribonucleotide; AMPK: AMP-activated protein kinase; ATG: autophagy related; BW: body weight; Cq: chloroquine; ER: endoplasmic reticulum; ESRD: end stage renal disease; FACS: fluorescence activated cell sorting; GFP: green fluorescent protein; i.p.: intra peritoneal; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; NPHS1: nephrosis 1, nephrin; NPHS2: nephrosis 2, podocin; PLA: proximity-ligation assay; PRKAA: 5ʹ-AMP-activated protein kinase catalytic subunit alpha; RPTOR/RAPTOR: regulatory associated protein of MTOR, complex 1; RFP: red fluorescent protein; TSC1: tuberous sclerosis 1; ULK1: unc-51 like kinase 1